2016 survey about temperature management during extracorporeal circulation in China. (April 2018) - Guo, Zhen; Li, Xin
Objective: In order to assess the current status of temperature management during cardiopulmonary bypass (CPB) in China and, thereby, implement standardized management protocols, the authors carried out a national survey about institutions performing CPB. Method: The survey was carried out from September 2015 to February 2016 and was supported by the Chinese Society of ExtraCorporeal Circulation. A total of 114 institutions participated, accounting for 15.64% (114/729) of the total of germane Chinese institutions, whereby, 80.85% (38/47) of the institutions had an annual surgical volume of more than 1000 cases. Results: The most common sites of temperature measurement were nasopharyngeal (NP) (99.12%) and rectal (92.98%) while oxygenator blood temperature was less popular (28%). Rectal temperature as the core temperature was chosen by 78.95% of the institutions; 92.11% of the institutions chose nasopharyngeal temperature to represent the cerebral temperature. During deep hypothermia circulatory arrest (DHCA) when there was no cerebral perfusion, 18 to 22℃ was the most common indication of circulatory arrest. However, with cerebral perfusion, more than 40% of the institutions maintained a lowest temperature of 22 to 25℃ for adult and pediatric patients. A NP temperature of 36 to 37℃ was chosen by 70.18% of the institutions while 81.79% chose a rectal temperature of 35 to 36.5℃ as the indication to wean from CPB. The majority of the institutions chose a difference of 10℃ between the water tank and core temperatures as the temperature gradient during rewarming. Auxiliary heat preservation techniques and equipment were used in 91.23% of the institutions, whereas 35.58% of them would lower the indications to wean from CPB. Conclusions: This survey accurately reflects the current situation of temperature management during CPB in institutions with an annual surgical volume of >500 cases, but has, hereby, failed to properly represent the institutions with a lower annual surgical volume.